FLGA Traffic Controller With Fuzzy Logic Algorithm: Fuzzy Traffic Controller - Lim, Khai Teng (2003)
This thesis describes a traffic controller design called Fuzzy Traffic Controller (FTC), which utilize fuzzy logic algorithm to achieve a smart and flexible knowledge-based system. It is a design of an intelligent fuzzy logic controller from Very High Speed Integrated Circuit Hardware Description Language (VHDL) description to field programmable Gate Array(FPGA) implementation that eliminates the shortcoming of other custom and conventional controller design available today.